The Relationship on Social Support with Anxiety in Stroke Patients - Faswita, Wirda (Talenta Publisher, 2021)
Around 90% of patients having stroke experience sudden weakness or paralysis of the limb. Other signs and symptoms include memory problems and some signs indicating impaired brain function. This study aims to determine the relationship between social support and anxiety levels of stroke patients dependent on daily activities using a dynamic correlation research design. This study's data sources are primary data and secondary data using a questionnaire instrument and analysis using chi-square test. The analysis of social support with the anxiety level of stroke patients dependent on daily activities shows that the p value = 0.184 (p> 0.05 then Ho is rejected, and Ha is accepted). This means no relationship exists between social support and anxiety levels in stroke patients who experience dependency on daily activities at RSUD Dr. RM Djoelham Binjai.